Disconnecting for the good: A network-oriented model for social contagion of opinions and social network interventions to increase adherence to social distancing - Araújo, Eric; Ferro, Mariza; Silva, Gabrieli (Anais do Brazilian Workshop on Social Network Analysis and Mining (BraSNAM), 2020)
The pandemic of the new COVID-19 has raised many questions to a very connected society as to how to best respond to such a challenge at this current time. The best response so far is to call people for following the instructions from the World Health Organisation (WHO) as a way of reducing the spread of the virus and thus relieving the health system, striving to avoid a collapse. This work studies the spread of positive opinion on adhering to social distancing based on network topology and metrics using a network-oriented model for social contagion. It is shown that interventions based on social network measurements can be used to boost the spread of positive opinion about adhering to these measures. It is also shown that our model accounts for the relevance the health authorities have on encouraging people to partake in social distancing voluntarily.